Politics and the Ruling Group in Putin's Russia - White, S.; White, S. (Studies in Central and Eastern Europe, 2008)
There is little consensus about the nature of the political system that has emerged during the Putin presidency. This collection considers the issues arising in this connection, focusing more closely on institutions such as the presidency and the security police, and on the socioeconomic dimensions of political power.